The viper [compact disc, unabridged] - Meltzer, Brad (Meltzer, Brad. Zig & Nola novel, 2026)
"Andrew Fechmeier is a master at hiding. He'd better be-he's spent decades concealing a secret that could get him killed. So when he's diagnosed with a terminal disease, he heads for the local funeral home carrying the blue suit he eventually wants to be buried in. But what no one knows is that Fechmeier secretly tucked something inside, turning the suit into a final, untraceable hiding spot. It's a perfect plan. Until Fetch is brutally murdered by a mysterious killer who will stop at nothing to find the priceless object hidden in the suit. Wasting no time, the cunning but unconventional police officer Roddy LaPointe opens an investigation into Fetch's murder, recruiting help from his friend, the brilliant 'Zig' Zigarowski. But it doesn't take long for Zig to discover the real reason Roddy cares so much about this case: Fetch's death is tied to Roddy's mother, who was murdered decades earlier. As the relentless killer closes in, Roddy's twin sister-the enigmatic and volatile Nola Brown-starts investigating for herself, uncovering a sinister plot that reveals their mother's dark history, the true identity of her killer, and the shocking secret behind her death"-- Provided by publisher.